Background and Scope of The Philosophy of Integrated Science Religion and Science and Their Goals and Benefits - Riskimilasari; Zulkifli Musthan (CV. Akademi Merdeka, 2026)
This study discusses the philosophy of science of integrating religion and science with an emphasis on its physiological and sociological background US well US its benefits and benefits. The study approach uses the library research method. The play data sources in this research are obtained from various references and research journals that are relevant and closely related to the issue of the integration of religion and science. All of the books and resources that have been successfully compiled are comprehensive guides that are relevant to the topics discussed. After the source collection process is completed, the next step is to analyze and synthesize the data to reach a valid conclusion from the results of this study. Physiologically, the relationship between modern science and religion has experienced dynamics from the 17th century to the 20th century from close encounters, views that reduce the role of God and the universe, to interactions that are dynamically re-formed. Sociologically, the integration of religion and science that was born in response to the dichotomy caused by the entry of secular western education into the Islamic world, resulted in two different educational systems, namely Islamic education and secular education. The philosophy of integrated science aims to create harmonization between religion and science, develop a holistic paradigm, strengthen Islamic epistemology and science, and develop an integrative educational curriculum. The benefits of this integration include moral and ethical foundations in the development of science and technology, motivating scientific research with religious nuances, bringing holistic and harmonious awareness in society, Reducing conflicts and dichotomies between religion and science.